Evaluation of statistical data on the use of volatile substances between 2011-2021 in Turkey - Akkaya, Nurhalime; Aktürk, İlker and Yaman, Ömer Miraç (Journal of Dependence, 2023)
This study was conducted to analyze data on inhalant users from studies in the last 10 years in Turkey. The lack of sufficient studies on the abuse of volatile substances in Turkey has led to the need for this study. In addition, since the studies conducted are mostly general studies on substance addiction, making it difficult to obtain detailed information about inhalant users, it was aimed to draw a picture of inhalant users in this study. The data was collected by searching for keywords from various search engines. The research was conducted with the systematic review method to evaluate the studies between 2011-2021. In the study, the studies conducted in Turkey were examined and the data were tabulated with a holistic approach. As a result of the examination, 202 studies were examined in depth. In the findings part of the research, the quantitative characteristics of the studies and the quantitative and qualitative characteristics of inhalant users are explained in detail. As a result of the study, it was seen that studies on inhalant users are mostly in the type of master’s thesis and articles, there are no comprehensive studies on the subject, and quantitative data are often found in studies on substance addiction. Studies dealing with the properties of volatile substances are generally case reports. Since the case reports do not represent large user groups, they do not allow to obtain comprehensive information. As a result of the study, it was thought that the subject should be brought to the agenda by the researchers because it was not adequately addressed in studies and because young children were a risk group.